OPTIMIZING MATERNAL AND CHILD HEALTH: ENHANCING PUBLIC AWARENESS OF TORCH INFECTIONS DURING PREGNANCY - Ekaputri, Tia Wida; Enis, Rina Nofri; Tarawifa, Susan; Harahap, Huntari; Syauqy, Ahmad; Perkasa, Tengku Arief Buana (Universitas Jambi, 2025)
TORCH infections (Toxoplasmosis, Rubella, Cytomegalovirus, Herpes simplex) pose significant risks during pregnancy, contributing to congenital abnormalities and adverse neonatal outcomes. In Indonesia, limited public awareness and inadequate preventive practices exacerbate these risks. This community service initiative aimed to enhance knowledge about TORCH infections among reproductive-aged women through a hybrid educational seminar. Conducted in collaboration with Peduli TORCH, the program utilized the